2014
DOI: 10.1055/s-0034-1372594
|View full text |Cite
|
Sign up to set email alerts
|

Markers of the Progression of Complications in Patients with Type 2 Diabetes: A One-year Longitudinal Study

Abstract: Hyperglycemia induces tissue damage and complications by mechanisms that produce advanced glycation end-products (AGEs) and inflammation.To investigate the factors associated with the progression of complications in Type 2 diabetes patients.We recruited 157 patients (110 women and 47 men) with diabetes for more than 5 years who were non-smokers and did not have current infections or chronic diseases. Patients were grouped according to neuropathy, nephropathy, and retinopathy status: without (I), slight or mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 18 publications
1
31
0
Order By: Relevance
“…Further, they found that higher levels of TNF-α were associated with both more advanced stages of retinopathy and albuminuria, as well as the presence of cardiovascular disease. This is further supported by a longitudinal study, though in type 2 diabetes, that found baseline TNF-α levels were positively associated with progression of complications over one year [34]. In light of our data indicating that higher C-peptide may predict lower TNF-α levels years later, and data from the DCCT demonstrating that higher residual C-peptide levels were associated with lower incidence rates of microvascular complications [35], TNF-α may be not only a marker for higher risk of complications, but may play a pathophysiological role in the progression of hypertension or microalbumiuria.…”
Section: Tnf-α and Diabetes-related Complicationsmentioning
confidence: 54%
“…Further, they found that higher levels of TNF-α were associated with both more advanced stages of retinopathy and albuminuria, as well as the presence of cardiovascular disease. This is further supported by a longitudinal study, though in type 2 diabetes, that found baseline TNF-α levels were positively associated with progression of complications over one year [34]. In light of our data indicating that higher C-peptide may predict lower TNF-α levels years later, and data from the DCCT demonstrating that higher residual C-peptide levels were associated with lower incidence rates of microvascular complications [35], TNF-α may be not only a marker for higher risk of complications, but may play a pathophysiological role in the progression of hypertension or microalbumiuria.…”
Section: Tnf-α and Diabetes-related Complicationsmentioning
confidence: 54%
“…18,19 Baseline circulating TNFa was a predictor of DR incidence, 20 as well as of diabetic complications progression. 21 In addition, a strong correlation between plasma levels of TNF-a and PDR has been reported. 22,23 However, Klein et al 24 reported that this correlation was mediated by the presence of kidney disease.…”
Section: Serum Biomarkers Related To Inflammation Circulating Proinflmentioning
confidence: 97%
“…Further, patient education to achieve understanding of the importance of adhering to what can be a complex preventive strategy [19], willingness, motivation and the domestic and workplace-related circumstances, may also be adversely affected by lower socio-economic status [18]. Identification of markers of progression of diabetes neuropathy is a critical area of research with impact on outcomes for many patients [20,21]. We also studied drug prescription patterns for painful neuropathy in our study population.…”
mentioning
confidence: 99%